Fostering Religiosity and Social Character through Islamic Educational Programs in the Context of Society 5.0 - Islamy, Mohammad Rindu Fajar (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2024)
This study aims to assess the effectiveness of the Islamic Religious Education Tutorial Program in enhancing students’ religiosity and social character. Drawing on Fromm’s theory, social character is critical in responding to societal changes, such as the digital revolution. Experts argue that technology and globalization have a profound impact on individual character in the context of Society 5.0. In this modern era, the importance of social character has become increasingly urgent due to rapid social transformations and the growing complexity of societal structures. These challenges include: 1) the rapid transformation of social structures, 2) social fragmentation, 3) the challenges posed by neoliberalism, and 4) the influence of social media and technology. This research employs a cross-sectional quantitative design, utilizing a Likert-scale questionnaire administered to 205 students from four different study programs at the Indonesia University of Education, Bandung, Indonesia. Data collected were analyzed using IBM SPSS software. The results indicate that the program led to significant improvements in seven key areas: 1) religious knowledge, 2) religiosity, 3) morality, 4) worship, 5) social responsibility, 6) empathy, and 7) tolerance. These improvements varied across study programs, with students enrolled in religious studies showing the most substantial increases in tolerance (average score 4.07) and religious knowledge (4.01). Notably, tolerance emerged as the most improved aspect overall. These findings highlight the program’s role as a vital tool for character development and propose a model for integrating moral education in the digital era of Society 5.0. Abstrak: Penelitian ini bertujuan untuk menilai efektivitas Program Tutorial Pendidikan Agama Islam dalam meningkatkan religiositas dan karakter sosial mahasiswa. Berdasarkan teori Fromm, karakter sosial sangat penting dalam merespons perubahan, seperti revolusi digital. Para ahli berpendapat bahwa teknologi dan globalisasi memiliki dampak yang signifikan terhadap karakter individu dalam konteks Society 5.0. Di era modern ini, urgensi karakter sosial semakin penting karena perubahan sosial yang cepat dan kompleksitas struktur masyarakat yang semakin meningkat. Tantangan-tantangan tersebut meliputi: 1) transformasi cepat struktur sosial, 2) fragmentasi sosial, 3) tantangan neoliberalism, dan 4) pengaruh media sosial serta teknologi. Penelitian ini menggunakan desain kuantitatif potong lintang, dengan menggunakan kuesioner skala Likert yang disebarkan kepada 205 mahasiswa dari empat program studi di Universitas Pendidikan Indonesia, Bandung, Indonesia. Data yang dikumpulkan dianalisis menggunakan perangkat lunak IBM SPSS. Hasil penelitian menunjukkan bahwa program ini memberikan peningkatan yang signifikan pada tujuh aspek: 1) pengetahuan agama, 2) religiositas, 3) moralitas, 4) ibadah, 5) tanggung jawab sosial, 6) empati, dan 7) toleransi. Peningkatan ini bervariasi di setiap program studi, dengan mahasiswa yang mengambil studi agama menunjukkan peningkatan terbesar pada aspek toleransi (skor rata-rata 4,07) dan pengetahuan agama (4,01). Secara keseluruhan, toleransi menjadi aspek yang paling meningkat. Temuan ini menegaskan peran program ini sebagai alat penting untuk pengembangan karakter dan memberikan model untuk mengintegrasikan pendidikan moral dalam era digital Society 5.0.